Laker: Art with Historical and Economic Value from The Land of Sriwijaya - Muhammad Reza Arviansyah; Farida R. Wargadalem; Helen Susanti; Sani Safitri (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2025)
Crafts are one of the factors that exist in culture, in this craft also has its own characteristics or uniqueness that represents the place or area where this craft exists and develops. Therefore, it includes a laker craft that is located and developing on Sriwijaya Earth. The characteristics in a craft certainly arise from historical similarities, cultural similarities, to environmental conditions. As one of the local wisdom owned by the people of Palembang, of course, this practice is mandatory for us to preserve so that it remains known by the nation's next generation of young people. So in this regard, the purpose of this authorship is to introduce lakuer which is seen from the point of view as a craft and local wisdom. Of course, in writing this article, the author uses qualitative research methods consisting of primary and secondary sources by collecting written data and analyzing the data that has been collected. Then for techniques in collecting data, namely carried out using observations, interviews, and literature studies which are certainly relevant to the theme to be discussed.